PENGARUH LINGKUNGAN INFORMAL TERHADAP HASIL BELAJAR SISWA SMP - Iftidah Dian Furaida; Nurlaily Azizah; Fayza Dwi Ega Leonida; Khuril ‘Aini; Firdha Yusmar; I Ketut Mahardika; Rizka Elan Fadilah (Pendidikan Fisika FKIP UNEJ, 2022)
The purpose of this study was to determine the effect of the informal environment on student learning outcomes. The method used in this study is a literature review where this method examines the relationship between the independent variable and the dependent variable. The independent variable in this study is the informal environment (X) while the dependent variable is student learning outcomes (Y). The success or failure of learning depends on the ongoing process. All parties must work together to promote student success in learning. The family environment is the first and most important environment that has the greatest influence on student learning outcomes. Informal environment can affect student learning outcomes. So that students can achieve learning outcomes that are in line with expectations, the family as a learning environment, the community environment is also a place that influences student learning outcomes that contribute to the teaching and learning process